Nutrition and Anxiety: Exploring Food's Role in Student Mental Health During Exams - Msc. Ban Yousif Yaaqoob (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Stress during university life is widely recognized as a major factor affecting students’ psychological well-being and dietary behavior. Specific Background: College students frequently experience heightened stress during examination periods, which may lead to changes in eating habits, appetite, and physical symptoms that can interfere with learning and daily functioning. Knowledge Gap: Despite growing research on student stress, limited evidence exists regarding nutrition awareness and food preferences during exam periods among students in health and medical technique programs in Baghdad. Aims: This study aimed to assess knowledge of healthy nutrition and examine food preferences and stress-related symptoms among college students during examinations. Results: A cross-sectional survey conducted from March 1 to April 30, 2025 revealed that 97% of students experienced anxiety accompanied by memory loss, 95% reported appetite changes, and 100% experienced headaches and stomach pain during exams. In terms of food preference under stress, 90% of students selected fast food, 74% preferred dark chocolate, and 60% consumed sweets. Meal skipping among male students showed strong association with stress and poor mood, while female students reported higher perceived stress and were more likely to engage in dietary changes such as binge eating. Novelty: The study provides empirical data linking exam-related anxiety symptoms with specific food choices and meal patterns among health college students in Baghdad. Implications: These findings highlight the need for nutritional awareness and stress management strategies within academic institutions to support student well-being during examination periods. Highlights:• High Prevalence of Anxiety Symptoms and Physical Complaints Reported During Examination Periods.• Stress Conditions Associated With Appetite Changes, Fast Food Preference, and Chocolate Consumption.• Gender Patterns Indicate Stronger Perceived Stress and Dietary Changes Among Female Students. Keywords: Exam Anxiety, Student Nutrition, Eating Habits, College Students, Academic Stress.